Evaluation consolidated under Financial Group Banca Transilvania - Chebac Neculina (EIRP Proceedings, 2009)
One of the components of prudence measures adopted by the competentauthorities with the regulation and supervision of financial markets at national andEuropean level is mandatory consolidation of accounts. Romania as member of theEuropean Union it harmonized national regulations with the European consolidation ofaccounts of companies. For the banks have been issued by the appropriate rules by theregulators authority, concerned by National Bank of Romania. In accordance withnational regulations, companies are required to prepare annual consolidated financialstatements may make such situations according to the regulations or accounting inaccordance with Directive VII of the European Economic Community, underInternational Financial Reporting Standards.